WORDPLAY TRANSLATION IN AUDIOVISUAL MEDIA: A COMPARATIVE ANALYSIS OF ENGLISH-UZBEK DUBBING IN ZOOTOPIA - Shakhnoza Pulatova Abdusamad kizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The  translation  of  wordplay  remains  one  of  the  most  challenging  aspects  of audiovisual translation due to the complex interaction between linguistic, cultural, and semiotic elements. This study investigates the translation strategies employed in the Uzbek dubbing of the animated film Zootopia, focusing on the rendering of English wordplay  into  Uzbek.  Audiovisual  texts  are  characterized  by  multimodal communication  in  which  verbal  expressions  are  closely  connected  to  visual  and acoustic  components.  Consequently,  translators  often  face  semiotic  constraints  that limit  the  possibility  of  preserving  the  formal  features  of  wordplay.  Using  Dirk Delabastita’s taxonomy of wordplay translation strategies as a theoretical framework, this study examines four examples extracted from the film and compares the source and  target  language  versions.  The  findings  reveal  that  the  Uzbek  dubbing predominantly  employs  the  Pun-to-Non-Pun  strategy,  prioritizing  pragmatic effectiveness  and  functional  adequacy  over  formal  linguistic  equivalence.  While phonetic and rhyming patterns present in the original English dialogue are frequently lost, translators compensate through descriptive adaptation, cultural localization, and visual anchoring. The study concludes that the linguistic differences between English and  Uzbek,  together  with  the  multimodal  constraints  of  audiovisual  translation, necessitate a shift from formal reproduction toward communicative effectiveness and audience comprehension.